A comparative floristic analysis of a cerrado area in Botucatu, State of São Paulo (Brazil) - Bicudo, LRH; Cesar, O.; Monteiro, R. (Inst Tecnologia Parana, 1996)
Based on the results of a phytosociological survey in a ''cerrado'' area located within the municipality of Botucatu, state of São Paulo Brazil, a comparative analysis of the 58 sampled tree species' is here presented using the data of other available floristics works for the ''cerrados in the same state. With a binary matrix of presence/absence of shared common species with the studied plot, a clustering analysis was performed thus obtaining a dendrogram which groups northern and southern areas with the same vegetation in the state of São Paulo previously treated as floristicaly differentiated. These results are discussed under the assumption that Isolated areas of ''cerrados'' are to be taken as targets for immediate conservation.
Keywords: cerrado; floristics; Brazilian savanna